(untitled) (American Journal of Islam and Society, 1989)
Introduction Current developments and the many acute problems facing the Muslim Ummah, especially at the intellectual level, present a serious challenge to Islam. This is why an attempt to outline an intellectual Islamic alternative in thought and knowledge has never been so urgent and imperative. Thi will, insha ’Allah, help in formulating a clear and coordinated policy with regard to cultural transformation based on firm principles and sound strategy. It is also hoped that this policy will lead to scientific findings. By way of introduction, I will give a brief description of the state of knowledge and thought. and of the educational and cultural systems in the contemporary Arab and Muslim world. The Present State of Thought When examining the present state of thought among the Muslim peoples. three basic approaches can be identified: • The first can be described as the traditionalist approach which, by and large, considers the "traditional’’ thought of the Ummah to be self-sufficient and capable of being presented as it is or with very little alteration. This approach suggests that the Ummah’s contemporary intellectual life can be formed and organized and that the structure of its civilization can be built on this basis. This approach i often described as the approach of authenticity. • The second approach considers contemporary Western thought and its world-view-its concepts of existence, of life and of man-to be universal, without it a modern culture and civilization cannot be built. This tendency maintains that Western thought must be adopted in toto, and any consequent negative aspects are the price that must be paid if a modern culture and civilization are to be established. This view is often described as mcdemistic. • The third trend, or the eclectic approach, advocates yet another view. It contends that one must select from traditional thought what is most sound, and from "modern" contemporary thought that which one considers and proves to be correct, and weld the two to form an intellectual structure that will provide a guaranteed basis for achieving what is required. However, the traditional approach, in the manner it has been presented and applied, did not help to prevent the Ummah from falling into Lhe state of decline and failure from which it is still suffering. Likewise, Western thought, as it also is presented and applied, cannot protect the Ummah from its inherent adverse, harmful and even disastrous effects. The advocates of the eclectic selective approach have not yet presented the details of this proposed blend, let alone tried to put it into effect. All this is conducive to the wideranging question: Is the Umrnah going through a serious intellectual crisis; and . if so, what is the way out of it? ...